Analysis of the Impact of Online Learning on Self-Development Students with Intellectual Disability in Family Perspective - Maulani Nurul Sofyan; M. Muktiarni; Jonah Mupita (JASSI ANAKKU, 2022)
This study purpose to determine the impact of online learning on the self-development ability of students with intellectual disabilities from a family perspective. The method used in this study is a mixed experimental method involving 8 parents of students with intellectual disabilities. This research stage is pre-test - treatment - post-test. As a result, there is no significant impact of online learning on the self-development ability of students with intellectual disabilities. Changes only occurred in the decrease in the habit of getting up early in the morning as much as 12.5% and the increase in the habit of studying regularly as much as 12.5%. Treatment in the form of learning videos of daily living activities only affected increasing students' morning habits by as much as 12.5%. This happens because students can take care and care for themselves independently. In addition, the limited time in treatment makes the results less than optimal. Online learning has both positive and negative impacts on students with intellectual disabilities. To reduce the negative impact, regular practice and collaboration between parents and teachers are needed so that students can achieve independence.